Explorando o uso de abstrações na implementação de controladores para sistemas a eventos discretos - Rosa, Marcelo (2016)
In the Supervisory Control Theory (SCT) of Discrete Event Systems, the refinement of events has been explored to simplify the modeling task. Approximations complement this approach as an alternative to reduce effort in synthesis. In spite of the advantages in the modeling and synthesis step, refinements do not directly cover the implementation phase. In general, controllers obtained with or without refinements are implemented with the same hardware cost. This paper proposes a decentralized architecture that extends the gains from the refinements of the synthesis to implementation. The proposed approach separates supervisor and distinguisher in two distinct structures, which communicate in such a way that the result of the control action on the plant is equivalent to the centralized version, but with reduced implementation cost. In addition, an alternative to implement the distinguisher behavior is presented using a generic two-state model, which is expected to extend to any distinguisher.